2020
DOI: 10.1186/s12889-020-08828-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the nutritional quality of products offered by the top packaged food and beverage companies in Canada

Abstract: Background: Canada's food supply is abundant in less healthy products, increasing Canadians' risk of obesity and non-communicable diseases. Food companies strongly influence the food supply; however, no studies have examined differences in the healthfulness of products offered by various companies in Canada. This study aimed to compare the nutritional quality of products offered by the top packaged food and beverage companies in Canada. Methods: Twenty-two top packaged food and beverage manufacturing companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Previous research demonstrated that many of the Canadian products offered by the packaged food and beverage companies in this sample are of relatively poor nutritional quality, with mean HSRs of <3.5/5 (i.e., generally considered less healthy) and two-thirds of their products exceeding 15% of the Daily Value and considered high in sodium, saturated fat, and/or sugars ( 6 ). There was also significant variation in the nutritional quality of comparable products offered by different companies ( 6 ). Similar results were observed in a 2016 cross-sectional analysis of calories and nutrients of concern in the menu items of major Canadian chain restaurants ( 64 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous research demonstrated that many of the Canadian products offered by the packaged food and beverage companies in this sample are of relatively poor nutritional quality, with mean HSRs of <3.5/5 (i.e., generally considered less healthy) and two-thirds of their products exceeding 15% of the Daily Value and considered high in sodium, saturated fat, and/or sugars ( 6 ). There was also significant variation in the nutritional quality of comparable products offered by different companies ( 6 ). Similar results were observed in a 2016 cross-sectional analysis of calories and nutrients of concern in the menu items of major Canadian chain restaurants ( 64 ).…”
Section: Discussionmentioning
confidence: 92%
“…In Canada, most major packaged food and beverage companies reported recent or ongoing actions to improve the nutritional composition of their products, with sodium being the most commonly targeted nutrient and a median score for the product (re)formulation policy domain of 27/100 ( 22 ). The nutritional quality of products offered by top packaged food and beverage companies in Canada, Australia, and New Zealand has also been assessed as part of BIA-Obesity phase 2 ( 6 , 14 , 27 ). However, the 2 phases have not yet been examined in combination to compare changes in the nutritional composition of companies’ products to their reported voluntary actions and commitments concerning product (re)formulation, in relation to WHO- and government-recommended targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data in Paraguay (n = 4,091) and Peruvian data (n = 1,533) were collected during the Summer 2017 and December 2019. The Canadian FLIP or the FLIP-LAC have been used for research, food supply monitoring, policy evaluation and modeling (28,(44)(45)(46)(47)(48).…”
Section: Flip Database In Other Countriesmentioning
confidence: 99%
“…Research has also shown that many of the products offered by major food companies are of relatively poor nutritional quality [ 24 , 25 , 27 – 30 ]. In Canada, two-thirds of products offered by the leading packaged food and beverage companies were energy-dense and high in sodium, saturated fat and/or sugars in 2017 [ 3 ]. These findings are not surprising, given the evidence to suggest the limited impact of government-led voluntary product (re) formulation policies on the healthfulness of the packaged food supply [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%